Six new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China - Su, Jing-Jing; Li, Xiao-Yan; Zhou, Hong-Zhang (Zootaxa, 2020)
This paper reports six new species of the genus Nazeris Fauvel, 1873 from mainland China, namely Nazeris lushanensis sp. nov., N. cuscutus sp. nov., N. baoxingensis sp. nov. and N. megalocephalus sp. nov. from Sichuan Province, N. fulongensis sp. nov. from Guangxi Province, and N. tarandoides sp. nov. from Hubei Province. For all new species included we offer color plates of normal light photos for general morphology and detailed aedeagus structures and one plate of heads of scan electromicroscope photos.